GOOD CORPORATE GOVERNANCE PERUSAHAAN TRANSPORTASI PADA KINERJA KEUANGAN - Widia Praptiwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study aims to determine the effect of good corporate governance which includes independent board of commissioners, managerial ownership, institutional ownership, board of directors and audit committee on financial performance. The method used is quantitative method. The type and used is secondary data in the form of financial reports obtained from the Indonesia Stock Exchange. Hypothesis testing using multiple regression analysis. The population in this study consisted of 46 transportation companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2023. The sampling method in this study used purposive sampling. A sample of 8 companies was obtained for 6 years. Data analysis techniques in this study using quantitative analysis techniques. The relationship used in this study is a causal relationship. The results of this study obtained that independent board of commissioners has a negative and insignificant effect on the financial performance of transportation companies in 2018-2023.Managerial ownership, institutional ownership, board of directors and audit committee have a significant positive effect on the financial performance of transportation companies in 2018-2023.